The Influence Of Viral Marketing And Prices On Purchasing Decisions At Fore Coffee Kediri - Syachnaz Putri Sagita Lestari; Ria Lestari Pangastuti; Wahyu Dede Gustiawan (Sean Institute, 2024)
The culture of drinking coffee is currently a new trend that has emerged in various groups of Kediri society. Fore Coffee is a coffee startup that is currently busy in Kediri. This research uses a quantitative method of surveying respondents via questionnaires with a total of 96 respondents. Based on the results of research on the influence of Viral Marketing and Price on Purchasing Decisions for Fore Coffee Kediri through distributing questionnaires, it can be concluded that Viral Marketing has no partial influence on the Purchasing Decision variable, while Price has a partial influence on the Purchasing Decision variable. However, if Viral Marketing and Price are combined, both have a significant influence on the Purchase Decision for Fore Coffee Kediri.